Influence of Nitrogen Level on Growth Pattern and Yield Performance of French Bean (Phaseolus vulgaris L.) in Nepal - Basnet, Dinesh Bahadur; Basnet, Komal Bahadur (International Journal of Applied Sciences and Biotechnology, 2022)
A field experiment was carried out with an objective to study the effect of nitrogen levels in the growth and yield performance of French bean (Phaseolus vulgaris L.) (PDR 14 or Uday) at Institute of Agriculture and Animal Science (IAAS), Rampur, Chitwan, Nepal from October 2008 to March 2009. The experiment of nitrogen levels was carried out with five treatments of 0, 40, 80, 120 and 160 kg/ha with three dates of sowing in three replications in split plot design. The soil of the experimental plots was sandy loam with acidic (pH 6.33) in nature. The effect of nitrogen levels on growth pattern and grain yield was found significant. Significantly higher grain yield was obtained with 120 kg N/ha (2.57 t/ha) as compared to control (1.39 t/ha), 40 (1.84 t/ha), 80 (2.04 t/ha) and 160 (2.01 t/ha) kg N/ha, respectively. The yield increased significantly with nitrogen up to 120 kg/ha and then declined at 160 kg/ha. So, in order to achieve higher productivity of French bean, 120 kg N/ha can be considered as an optimum level of nitrogen application in the humid sub-tropical condition of inner Terai, Chitwan of Nepal.Int. J. Appl. Sci. Biotechnol. Vol 10(1): 31-40.